Use of verbal autopsy in a national health information system: Effects of the investigation of ill-defined causes of death on proportional mortality due to injury in small municipalities in Brazil - Souza Maria de Fátima M; Campos Deise; Guimarães Mark DC; França Elisabeth (BMC, 2011)
Abstract Background The Mortality Information System (MIS) in Brazil records mortality data in hospitals and civil registries with the responsibility of compiling underlying cause of death. Despite continuous improvements in the MIS, some areas still maintain a high proportion of deaths assigned to ill-defined causes. Deaths coded to this category have most likely been considered as miscoded deaths from communicable and noncommunicable diseases. However, some local studies have provided evidence of underreporting of injury in Brazil. The aim of this study was to investigate ill-defined causes of death using the verbal autopsy (VA) method to estimate injury-specific mortality fraction in small municipalities in northeastern Minas Gerais, Brazil. Methods A sample size of reported death certificates with ill-defined conditions in a random sample of 10 municipalities was obtained, and then trained interviewers questioned family members using a standardized VA questionnaire to elicit information on symptoms experienced by the deceased before death. All attempts were made to collect existing information about the disease or death using health facilities records. Probable causes of death were assigned by a physician after review of the completed questionnaires following rules of the 10th revision of the International Classification of Diseases (ICD-10). Results Of 202 eligible ill-defined deaths, 151 were investigated using the VA methodology, and 12.6% had injury as the underlying cause of death. The proportional mortality fraction from injury among all causes of death increases from 4.4% to 8.2% after investigation. Different specific injury category causes were observed between recorded injury causes and those detected by VA. Drowning was the top specific injury cause detected after investigation. Conclusions This study provides evidence that the use of VA in the investigation of registered ill-defined conditions in an existing MIS can furnish information on the relevance of injury as a priority health problem in small municipalities of Minas Gerais. Local research with VA should be brought to the attention of regional health policymakers to improve the quality of data for their planning.